The landscape of educational technology viewed from the ETR&D journal. (6th July 2012) - Cho, Yonjoo; Park, Sunyoung; Jo, Sung Jun; Suh, Susan
Abstract: The purpose of this study was to conduct a citation network analysis of Educational Technology Research and Development (ETR&D) to examine the trends and issues of the educational technology field's scholarly community that have evolved in the past two decades. The distinctive features of citation network analysis used in this study derive from a social network analysis approach to see relational and network patterns in the citation data. From this citation network analysis, we obtained the following results: (1) the ETR&D network revealed structural attributes that help us understand the features regarding how the field has developed and how scholarly works have interacted; (2) the most influential papers and scholars in the field were identified; (3) frequently co‐cited papers were recognized as having a strong relationship by a few researchers and (4) five cohesive subgroups (factions) generated key research themes in the field including: instructional design, learning environments, the role of technology, educational technology research and psychological foundations. Implications and limitations of the study were discussed for future research.